2020
DOI: 10.1177/0267659120906046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delayed systemic heparinization on postoperative bleeding and thromboembolism during post-cardiotomy extracorporeal membrane oxygenation in neonates

Abstract: Introduction: Veno-arterial extracorporeal membrane oxygenation is well-established for pediatric patients with post-cardiotomy heart failure. However, extracorporeal membrane oxygenation support is associated with major complications, that is, hemorrhage and thromboembolism. We seek to report our experience with delayed systemic heparinization during neonatal cardiac extracorporeal membrane oxygenation and its impact on bleeding and thromboembolism. Methods: We retrospectively identified 15 consecutive neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Our centre has followed a similar approach, and we tend to delay heparinization even more in order to avoid haemorrhagic complications in patients on PC-ECLS. Von Stumm et al reported no increase in thromboembolic events and a potential reduction of bleeding events with delayed heparinization in neonatal patients on PC-ECLS [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our centre has followed a similar approach, and we tend to delay heparinization even more in order to avoid haemorrhagic complications in patients on PC-ECLS. Von Stumm et al reported no increase in thromboembolic events and a potential reduction of bleeding events with delayed heparinization in neonatal patients on PC-ECLS [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, von Stumm et al (12) explored delayed systemic heparinization in 15 neonatal post-cardiotomy ECMOs for which the average UFH start time was 18.1±9.3 h. They found that delayed continuous UFH infusion could reduce bleeding and blood product transfusion without increased risk of thrombosis. This seems to be a bit different from our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This high bleeding tendency leads to a clinical dilemma in choosing anticoagulation regimens, as there is no unified recommendation for practices related to peri-CPB unfractionated heparin (UFH) in pediatric VA-ECMO up until now (10,11). While some centers have adopted a strategy of delayed systemic heparinization (12), conclusions regarding its safety and practicability cannot be drawn due to insufficient patient numbers.…”
Section: Introductionmentioning
confidence: 99%
“…4 In response to complications such as ICH and surgical site bleeding, efforts have been made to reduce the level of anticoagulation required, including the development of heparin-coated centrifugal pump systems allowing delayed initiation of anticoagulation, 12 and electing to delay anticoagulation when possible until chest tube drainage decreases in postoperative congenital cardiac patients. 8 In addition to these steps, frequent neuromonitoring is often performed, with common practice being to obtain daily HUS in infants on ECLS although the utility of this practice has been questioned. In a study of 30 infants who developed ICH on ECLS from 1996, 85% of all ICH occurred within 72 hours of ECLS initiation.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, most of the research on this topic is now over 2 decades old, and there have been critical advancements and modifications in the management of patients on ECLS, such as reductions in anticoagulation target levels, with some patients undergoing anticoagulation-free trial periods following cannulation. 8 Furthermore, advances in ultrasound imaging technology and neonatal and pediatric critical care may have altered the prevalence and timing of ICH development and diagnosis in this patient population. It remains unknown if the advances over the past 2 decades have resulted in earlier detection of ICH in this population.…”
mentioning
confidence: 99%